ALDH2 Overexpression Alleviates High Glucose-Induced Cardiotoxicity by Inhibiting NLRP3 Inflammasome Activation - Ruiping Cao; Dian Fang; Jiahui Wang; Ying Yu; Hongwei Ye; Pinfang Kang; Zhenghong Li; Hongju Wang; Qin Gao (Journal of Diabetes Research)
Although the underlying mechanisms of diabetes-induced myocardial injury have not been fully illuminated, the inflammation reaction has been reported intently linked with diabetes. The nucleotide binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome, the key component of pyroptosis, is involved in inflammation reaction, which may be one of the important mechanisms in diabetes-induced myocardial injury. The purpose of this study was to investigate the changes of NLRP3 inflammasome and pyroptosis in high glucose-induced H9C2 cardiac cell injury and investigate whether overexpression of mitochondrial aldehyde dehydrogenase 2 (ALDH2) can reduce the occurrence of pyroptosis. The H9C2 cardiac cells were exposed to 35 mM glucose for 24 h to induce cytotoxicity. Mitochondrial ALDH2 overexpression cardiac cell line was constructed. The results showed in high glucose condition that ALDH2 overexpression significantly increased H9C2 cardiac cell viability, increased mitochondrial ALDH2 activity and protein expression, and reduced mitochondrial reactive oxygen species (ROS) production, 4-hydroxynonenal (4-HNE), and lactate dehydrogenase (LDH) levels; meanwhile, the pyroptosis key components—NLRP3 inflammasome-related proteins, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), cysteine-containing aspartate specific protease 1 (Caspase-1), and interleukin-18 (IL-18) protein expressions—were significantly decreased, and IL-18 and interleukin-1β (IL-1β) levels were also decreased. In high glucose-induced cardiac cell injury, ALDH2 overexpression may reduce ROS production, thereby inhibiting the activation of NLRP3 inflammation and cell pyroptosis. ALDH2 gene might play the potential role in the treatment of high glucose-induced H9C2 cardiac cell injury.